The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2224/sbp.10381
|View full text |Cite
|
Sign up to set email alerts
|

Social support and social commerce purchase intention: The mediating role of social trust

Abstract: Social commerce (s-commerce) has risen in popularity primarily owing to social media development. We investigated social support as a predictor of s-commerce purchase intention, and the mediating role of social trust in this relationship. Participants comprised 356 undergraduate students at five Chinese public universities. Structural equation modeling results indicate that social support had a direct positive effect on s-commerce purchase intention, and that social trust partially mediated this relationship.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…According to Alalwan et al (2019) and Kim and Park (2013), trust mediates the relationships between s-commerce dimensions and consumers' value co-creation, and between the characteristics of s-commerce and purchase intention. Liu et al (2021d) confirmed that social support had a direct positive effect on s-commerce purchase intention, and that social trust partially mediated the relationship. From this, it can be hypothesized that consumers generate trust by watching tourism e-commerce live streaming and generate purchase intention under the influence of trust.…”
Section: The Mediating Role Of Trustsupporting
confidence: 53%
“…According to Alalwan et al (2019) and Kim and Park (2013), trust mediates the relationships between s-commerce dimensions and consumers' value co-creation, and between the characteristics of s-commerce and purchase intention. Liu et al (2021d) confirmed that social support had a direct positive effect on s-commerce purchase intention, and that social trust partially mediated the relationship. From this, it can be hypothesized that consumers generate trust by watching tourism e-commerce live streaming and generate purchase intention under the influence of trust.…”
Section: The Mediating Role Of Trustsupporting
confidence: 53%
“…Another goal of this study is to examine whether PSS and RSS moderate the indirect relationship between exposure to news about COVID-19 and stress through social trust. Individuals with more social support may have better views about general others (Liu et al, 2021), which offers them more confidence in stress coping. Although individuals may not always receive the support they find helpful (Lehman et al, 1986), the act of providing support functions as an expression of concern for the support recipients (Semmer et al, 2008).…”
Section: Stress Buffering Of Pss and Rss Through Social Trustmentioning
confidence: 99%
“…The overall motivational factors are constructed by multiple variables, explicitly referring to utilitarian motivation, hedonic motivation, and perceived value. Perceived value is an essential motivational factor in recent research (X. Liu et al, 2021; Peng et al, 2019), normally considering the effect of both utilitarian and hedonic motivation factors on CPI (Xia & Chae, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%